SUCCESS OF GUIDELINES AND COUNSELING SERVICES REVIEWED FROM THE COMPETENCY OF CONSELOR PERSONALITY AND INFRASTRUCTURE FACILITIES - Permadani, Fisrty; Widodo, Bernardus (Educatio Vitae, 2020)
This study aims to determine the effect of counselor personality competence and infrastructure on the success of counseling and guidance services. The population of this research is the Counselors of Madiun City Junior High School in the academic year 2019/2020, amounting to 36 counselors. The technique used is Saturated Sampling. Data were analyzed using multiple linear regression techniques. Based on the results of data processing it can be concluded as follows: (1) Correlation analysis has a strong closeness with an R number of 0.861, (2) Hypothesis "There is a significant influence on the counselor's personality competency on the success of guidance and counseling services", accepted because t arithmetic> t table = (4,549> 1,692), (3) Hypothesis "There is a significant influence of infrastructure on the success of guidance and counseling services", rejected because t arithmetic <t table = (-1.606 <1,692), (4) Hypothesis "There is a significant influence counselor personality competence and infrastructure for the success of guidance and counseling services "accepted because F count> F table=(47,120>3.28). Keywords: success of counseling and guidance services, counselor personality competence, infrastructure.